Prevalence of Adverse Effects Associated With Transcranial Magnetic Stimulation for Autism Spectrum Disorder: A Systematic Review and Meta-Analysis - Huashuang, Zhang; Yang, Li; Chensheng, Hou; Jing, Xin; Bo, Chen; Dongming, Zhang; Kangfu, Liang; Shi-Bin, Wang (Frontiers in Psychiatry, 2022)
Background: A growing number of studies have suggested transcranial magnetic stimulation (TMS) may represent a novel technique with both investigative and therapeutic potential for autism spectrum disorder (ASD). However, a full spectrum of the adverse effects (AEs) of TMS used in ASD has not been specifically and systematically evaluated. Objectives: This systematic review and meta-analysis was to assess the prevalence of AEs related to TMS in ASD, and to further explore the potential related factors on the AEs. Methods: A systematic literature research of articles published before 31 December, 2020 was conducted in the databases of PubMed, Embase, Cochrane Library, Ovid, PsycINFO, Chinese National Knowledge Infrastructure (CNKI), Chongqing VIP and WANFANG DATA. AEs reported in the studies were carefully examined and synthesized to understand the safety and tolerability of TMS among ASD. Then subgroup and sensitivity analysis were performed to examine the potential related factors on the AEs. PROSPERO registration number: CRD42021239827. Results: Eleven studies were included in the meta-analysis. The pooled prevalence with 95% confidence interval (CI) of AEs were calculated (overall AEs: 25%, 95% CI 18-33%; headache: 10%, 95% CI 3-19%; facial discomfort: 15%, 95% CI 4-29%; irritability 21%, 95% CI 8-37%; pain at the application site: 6%, 95% CI 0-19%; headedness or dizziness: 8%, 95% CI 0-23%). All reported AEs were mild and transient with relatively few serious AEs and can be resolved after having a rest or medication. In addition, the following variables showed no significant change in overall prevalence of AEs: the purpose of using TMS, mean age of participants, whether the stimulation site was dorsolateral prefrontal cortex (DLPFC), intensity of TMS and the number of stimulation sessions. Conclusion: The overall prevalence of reported AEs of TMS among ASD was 25%. No identified ASD-specific risk factors for TMS-induced AEs were found. Further studies are needed to clarify the variation in the prevalence.